The proprioceptive puzzle: An observational study investigating the effects of cervical proprioceptive errors on quantitative sensory testing and body awareness in young individuals - Nagihan Acet; Sena Begen (PLoS ONE, 2025)
Objective The present study investigates the effects of cervical proprioceptive errors (CPE) on body awareness and quantitative sensory testing (QST), including the pressure pain threshold, temporal summation, and conditioned pain modulation in young individuals. Materials and methods Included in this prospective cross-sectional study were 78 participants who were divided into two groups based on the presence or absence of CPE. The study was registered on ClinicalTrials.gov with the clinical trial number [NCT06559397]. Cervical proprioception was measured using the “head position error test”, body awareness was assessed using the “Body Awareness Questionnaire”, QST was assessed using a mechanical pressure algometer, and conditioned pain modulation was evaluated using cold stimulus. Results The study revealed a significant reduction in body awareness among those with CPE (p < 0.001), while no significant differences were found between the groups in terms of QST, including the pressure pain threshold, temporal summation, and conditioned pain modulation (p > 0.05). Conclusions CPE can have a significant impact on body awareness, leading to a decrease in the ability to perceive one’s own body. While the present study offers no significant findings related to QST, it provides new insights into the relationship between proprioception, body awareness, and pain processing mechanisms. Clinically, the results suggest the importance of integrating interventions aimed at enhancing body awareness into the treatment protocols of patients with CPE.